KONDISI SOSIAL EKONOMI KARYAWAN PERTERNAKAN AYAM RAS PETELUR DI KOTO BARU NAGARI MUNGKA KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - M, Rhagel Anugerah; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The purpose of this research is to determine the basic fulfillment of employees of egg-laying breed chicken farms in Koto Baru Nagari Mungka, Mungka District, Limapuluh Kota Regency, to determine the income of employees of egg-laying breed chicken farms in Koto Baru Nagari Mungka, Mungka District, Limapuluh Kota Regency, and to determine fulfillment. principal employees of the Laying Breed Chicken Farm in Koto Baru Nagari Mungka, Mungka District, Limapuluh Kota Regency. This research uses a mixed methods research method, which combines quantitative and qualitative forms. The research results show that the employee payroll system at the laying hen farm in Koto Baru, Nagari Mungka uses a daily wage, weekly wage and monthly wage system, where daily wages are calculated based on the number of eggs produced each day. The income and salary system provided by owners of egg-laying chicken farming businesses in Koto Baru, Nagari Mungka, there are still many employees who feel dissatisfied with the salary system because they feel it is not enough to meet their daily needs and the need for food, clothing and shelter. The employees of the Koto Baru egg laying chicken farm, Nagari Mungka are not yet fulfilled but can be said to be quite prosperous.